EVALUASI KINERJA RAMBU PEMBATASAN KECEPATAN SEBAGAI UPAYA MENDUKUNG AKSI KESELAMATAN JALAN - Teja Murti, Rialiska; Muthohar, Imam (Jurnal Transportasi, 2012)
One of the main causes of traffic accidents are noncompliance motorists, which include driving at high speed regardless of traffic signs indicating motor vehicle speed limit. This study discusses and evaluates the road characteristics and speed of road users, especially motor vehicles and the performance of the speed limit signs on Kapten Haryadi street, and the perception of road users for non-compliance with the signs in place. The method used is direct field surveys such as traffic survey, the survey speed with a local method using a Speed Gun, and a survey using a questionnaire. The results show that the total flow (Q) is 1771.2 pcu/hr, free flow velocity (FV) is 58,65 km/hr, road segment capacity (C) is 2883 smp/hr, and the degree of saturation is 0.614. Furthermore. It is shown that many violations of the speed limit signs occur in in Kapten Haryadi road segmen.Keywords: speed limit, traffic accidents, traffic violation.